Exact algorithm for bi-objective 0-1 knapsack problem - Jolai, Fariborz; Rezaee, M.J.; Rabbani, M.; Razmi, J.; Fattahi, Pariviz (Applied mathematics and computation, 2007)
In this paper, we propose a new procedure based on linear mathematical programming formulation to find all efficient solutions of bi-objective 0-1 knapsack problem. We solve a limited number of single objective problems to find efficient solutions of bi-objective 0-1 knapsack problem. We show that the proposed method is able to generate efficient solutions with less constraints and variables than the general linear program found in the literature. An example is presented to illustrate the steps of the procedure.